2019
DOI: 10.1159/000498835
|View full text |Cite
|
Sign up to set email alerts
|

Torpedo Maculopathy Associated with NEXMIF Mutation

Abstract: Mutations in the neurite extension and migration factor (<i>NEXMIF</i>) gene are associated with X-linked intellectual disability. Thus far, all males reported with <i>NEXMIF</i> mutations have mild to profound intellectual disability with varying combinations of autistic features, poor or absent speech, epilepsy, facial dysmorphism, and strabismus. Affected females tend to have milder intellectual disability but severe, drug-resistant epilepsy. Here, we present a 32-month-old boy with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…These patients showed repetitive behaviors, impaired language, seizures, and ID, with several cases of microcephaly (Cantagrel et al, 2004(Cantagrel et al, , 2009Van Maldergem et al, 2013). Multiple additional reports have confirmed the loss of NEXMIF by gene mutation or deletion in ASD patients (Charzewska et al, 2015;Kuroda et al, 2015;Farach and Northrup, 2016;Webster et al, 2017;de Lange et al, 2016;Lambert et al, 2018;Lorenzo et al, 2018;Alarcon-Martinez et al, 2019). NEXMIF has been listed as an ASD gene in the SFARI database.…”
Section: Introductionmentioning
confidence: 92%
“…These patients showed repetitive behaviors, impaired language, seizures, and ID, with several cases of microcephaly (Cantagrel et al, 2004(Cantagrel et al, , 2009Van Maldergem et al, 2013). Multiple additional reports have confirmed the loss of NEXMIF by gene mutation or deletion in ASD patients (Charzewska et al, 2015;Kuroda et al, 2015;Farach and Northrup, 2016;Webster et al, 2017;de Lange et al, 2016;Lambert et al, 2018;Lorenzo et al, 2018;Alarcon-Martinez et al, 2019). NEXMIF has been listed as an ASD gene in the SFARI database.…”
Section: Introductionmentioning
confidence: 92%
“…Female patients with 100% skewed X-inactivation patterns show severe intellectual disability resembling the male phenotype [de Lange et al, 2016]. A male patient with the hemizygous mutation c.1123del (p.Glu-375Argfs*21) in NEXMIF not only has milder motor developmental delay, facial dysmorphic features, and no DOI: 10.1159/000510172 episodes of epilepsy compared with other male patients, but also has torpedo maculopathy and increased extraaxial space, which were not observed in our patient [Alarcon-Martinez et al, 2019]. The X-inactivation pattern in our patient (60:40) and the milder phenotype in male patients with the same mutation in NEXMIF were compatible with our patient's milder intellectual disability and epilepsy.…”
Section: Discussion/conclusionmentioning
confidence: 46%
“…1c, d). We performed trio whole-exome sequencing as previously described elsewhere [Aoi et al, 2019] and identified a heterozygous de novo mutation, c.1123del (p.Glu375Argfs*21), in NEXMIF, which was previously reported in a male patient [Alarcon- Martinez et al, 2019]. We confirmed the mutation by Sanger sequencing.…”
Section: Case Presentationmentioning
confidence: 63%
See 1 more Smart Citation
“…NEXMIF was first studied as a candidate gene in two male members of a family who presented with autistic features and intellectual disabilities (ID) [ 10 ]. Since this original diagnosis, more cases have been reported, confirming that a loss of NEXMIF protein due to NEXMIF gene mutation or deletion leads to ASD [ [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. The reported individuals with NEXMIF -dependent ASD show impaired communication, repetitive behaviors, seizures, ID, and microcephaly.…”
Section: Introductionmentioning
confidence: 99%